2014
DOI: 10.1007/s13644-014-0169-y
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering and the Dimensions of Religiosity: A Cross-National Analysis

Abstract: Religion and volunteerism are closely linked, but which aspects of religiosity matter most for volunteering? This article predicts volunteering with a multi-dimensional model of private and public religiosity using a sample of 9,464 respondents from 15 Western European countries. An interaction between private and public religiosity is also theorized and tested. Three dimensions of private religiosity (religious salience, prayer, and belief) are significant in predicting volunteering, and each has a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 71 publications
6
70
0
6
Order By: Relevance
“…There have been several general studies of volunteerism published since the onset of the Great Recession [18][19][20][21][22][23][24][25][26][27][28][29][30]. This research found a wide range of factors other than race correlated with volunteerism.…”
Section: Researchmentioning
confidence: 88%
“…There have been several general studies of volunteerism published since the onset of the Great Recession [18][19][20][21][22][23][24][25][26][27][28][29][30]. This research found a wide range of factors other than race correlated with volunteerism.…”
Section: Researchmentioning
confidence: 88%
“…[39] and how these distinct forms of religiosity might affect volunteering behaviors [40]. Considerable attention has been given to private forms of religiosity, through a focus on beliefs and psychological dispositions in motivating volunteerism [26,41].…”
Section: Volunteerism and Religiositymentioning
confidence: 99%
“…Paxton et al (2014) eredményei azt mutatják, hogy az egyéni vallásgyakorlat (pl. rendszeres imádkozás) pozitív hatással van az önkéntességre.…”
Section: A Vallásosság Dimenziói éS Az öNkéntesség Kapcsolataunclassified
“…A templomba járás olyan társadalmi interakciókkal is jár, amelyek segítenek információt szerezni az önkénteskedési lehető-ségekről, valamint megnövelik annak az esélyét, hogy valakit önkéntes tevékenységben való részvételre kérjenek (Wilson 2000). A szociális hálózatok ráadásul elősegítik a társadalmi bizalmat, illetve megnövelik a nyitottságot az embertársak szükségletei és az állampolgári szerepvállalás iránt (Prouteau & Sardinha 2015;Paxton et al 2014). Az egyházi tevékenységekben való részvétel azért is segíti elő az önkéntességet, mert a vallási csoportok olyan értékeket kínálnak, amelyek a közösség tagjai iránti jótékony-kodásra buzdítanak, valamint a templomban az odajárók tájékozódhatnak is a konkrét önkénteskedési lehetőségekről (Mattis et al 2000).…”
Section: A Vallásosság Dimenziói éS Az öNkéntesség Kapcsolataunclassified
See 1 more Smart Citation